Quasi-spherical nano-cerium dioxide and its suspension, preparation method and application
The spherical nano ceria is prepared through the high-temperature step-by-step synthesis process of composite precipitant, which solves the defects and flatness problems during the polishing process, and achieves efficient polishing effect and particle uniformity, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202211492390.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-25
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-11-25
AI Technical Summary
In the chemical mechanical polishing process, the prior art is difficult to avoid defects during polishing and improve surface flatness, especially the problems of particle agglomeration, poor hardness uniformity, and difficult to control the morphology after burning at high temperatures.
The high-temperature step-by-step synthesis process of composite precipitant is prepared by adding soluble carbonate and alkali to the cerium salt solution to form a cerium dioxide precursor, and hydrothermal crystallization and calcination are carried out to prepare spherical nano cerium dioxide. Combined with ultrasound, high-speed fluid collision or mechanical force of a sand mill, it is evenly dispersed to form a suspension.
It realizes precise control of the morphology and size of spherical nano ceria, avoids particle agglomeration, improves polishing efficiency and surface flatness, and is suitable for integrated circuit manufacturing and ultra-precision polishing of optical glass.
Smart Images

Figure CN115974127B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of chemical mechanical polishing, and in particular to spherical nano-cerium dioxide and its suspension, preparation method and application. Background Art
[0002] The main components of chemical mechanical polishing liquid are abrasive particles, which generally include cerium dioxide, silicon dioxide, aluminum oxide, etc., as well as corrosive media, oxidants, co-oxidants, pH regulators, etc. In particular, cerium dioxide, as a polishing abrasive, can be used for polishing silicon wafers and silicon dioxide dielectric films, as well as for polishing organic polymers, high and low dielectric films, and shallow trench isolation layers. Its application range is quite wide. Cerium dioxide abrasive has the advantage of fast polishing rate, which is mainly due to the fact that CeO 2 The chemical action of particles during polishing causes CeO 2 The crystal shape and activity are good, with the advantages of small and uniform particle size, small dosage and long service life; CeO 2 It also has the excellent properties of not polluting the polishing environment, good working conditions, and being non-toxic.
[0003] Since the roughness of the polished surface is proportional to the cutting depth of the embedded matrix, the surface can obtain extremely low surface roughness after polishing with nano-cerium dioxide abrasives, showing a good polished surface with good polishing finish, stable layer brightness and easy cleaning. And the closer the nano-cerium dioxide particles are to spherical, the better it is for avoiding defects and surface flatness when used for polishing. Summary of the invention
[0004] The purpose of the present application is to provide a spherical nano-cerium dioxide, aiming to avoid defects during polishing and improve the flatness of the surface.
[0005] To achieve the above objectives, the present application provides a method for preparing spherical nano-cerium dioxide, comprising:
[0006] Preparation of cerium dioxide precursor: adding a composite precipitant solution to a cerium salt solution to react and obtain a cerium dioxide precursor, wherein the composite precipitant solution includes a soluble carbonate and an alkali solution;
[0007] Hydrothermal crystallization of a cerium dioxide precursor: hydrothermally crystallizing the cerium dioxide precursor to obtain crystallized cerium carbonate;
[0008] Calcination of crystallized cerium carbonate: calcining the crystallized cerium carbonate to obtain the spherical nano-cerium dioxide.
[0009] Preferably, the composite precipitant solution comprises at least one of the following features:
[0010] a. The molar concentration ratio of the soluble carbonate to the alkali solution in the composite precipitant solution is 1: (0.01 to 2.0);
[0011] b. The soluble carbonate is selected from ammonium bicarbonate or sodium bicarbonate;
[0012] c. The alkali solution is selected from any one or more of ammonia, secondary amines, tertiary amines, quaternary amines, sodium hydroxide, potassium hydroxide, alkali metals and alkaline earth metal hydroxides;
[0013] d. The soluble carbonate is selected from ammonium bicarbonate; the alkali solution is selected from any one or more of ammonia water, secondary amine, tertiary amine and quaternary amine.
[0014] Preferably, the step of adding a composite precipitant solution to a cerium salt solution to obtain a cerium dioxide precursor comprises:
[0015] The cerium salt solution is heated to 60-90° C.;
[0016] Adding the composite precipitant solution to the cerium salt solution at a flow rate of 5 to 30 ml / min until the pH of the mixed solution reaches 5.5 to 7.5, and then stopping adding the composite precipitant solution;
[0017] Keep warm and age for 1 to 6 hours.
[0018] Preferably, the cerium ion concentration in the cerium salt solution is 0.1 to 1.5 mol / l;
[0019] The carbonate concentration in the composite precipitant solution is 0.3-3 mol / l.
[0020] Preferably, the hydrothermal crystallization of the cerium dioxide precursor to obtain crystallized cerium carbonate comprises:
[0021] The cerium dioxide precursor is heated to 80-200° C. and heat treated for 2-48 hours;
[0022] Cooling, washing and drying to obtain the crystallized cerium carbonate;
[0023] Preferably, the ceria precursor is heated to 120-200° C. and heat treated for 4-14 hours.
[0024] Preferably, the step of calcining the crystallized cerium carbonate to obtain the spherical nano-cerium dioxide comprises:
[0025] The crystallized cerium carbonate is calcined at 550-950° C. in an air atmosphere for 1-5 hours to obtain the spherical nano-cerium dioxide.
[0026] Preferably, the preparation method comprises at least one of the following features:
[0027] a. adding a surfactant having a cerium oxide content of 0.05 to 0.5% to the cerium salt solution;
[0028] b. The surfactant comprises an ionic surfactant and / or a nonionic surfactant;
[0029] c. The surfactant is selected from polyvinyl pyrrolidone;
[0030] d. The surfactant is selected from PVP-K30.
[0031] The present application also provides a quasi-spherical nano-cerium dioxide, which is prepared by the above-mentioned method for preparing quasi-spherical nano-cerium dioxide;
[0032] Preferably, the spherical nano-cerium dioxide comprises at least one of the following features:
[0033] a. The specific surface area of the spherical nano-cerium dioxide is 4-40m 2 / g;
[0034] b. The spherical nano-cerium dioxide is a secondary particle formed by agglomeration of primary particles, and the D50 of the primary particles is 20 to 400 nm;
[0035] c. The D50 of the secondary particles is 60-1000nm.
[0036] The present application also provides a method for preparing a quasi-spherical nano-cerium dioxide suspension, wherein the quasi-spherical nano-cerium dioxide is prepared into a slurry with a solid content of 5 to 50%, a dispersant is added, and the quasi-spherical nano-cerium dioxide is deagglomerated and uniformly dispersed in a medium under the action of any mechanical force such as ultrasound, high-speed fluid collision or a sand mill, and the quasi-spherical nano-cerium dioxide suspension is obtained by filtering.
[0037] The present application also provides a quasi-spherical nano-cerium dioxide suspension, which is prepared by the above-mentioned method for preparing a quasi-spherical nano-cerium dioxide suspension; the quasi-spherical nano-cerium dioxide in the suspension has a dispersion index of 0.20 to 0.80.
[0038] The present application also provides the use of the above-mentioned spherical nano-cerium dioxide in chemical mechanical polishing, ultraviolet sun protection, catalysts, ceramic preparation, and surface polishing of glass and gemstone crystals.
[0039] Compared with the prior art, the beneficial effects of this application include:
[0040] The preparation method of spherical nanometer cerium dioxide provided by the present application uses a composite precipitant high temperature step-by-step synthesis process, which is easy to control, has high stability, and can accurately control the morphology and size of the synthesized particles. The crystallized cerium carbonate prepared using this process technology has the advantages of spherical particle morphology, nanometer monodisperse characteristics, and good particle uniformity, and the particle morphology, size, and dispersion state of cerium carbonate will not change after high temperature calcination treatment, and has genetic inheritance, and can accurately control the morphology of spherical nanometer cerium dioxide. Compared with the traditional process, it avoids the shortcomings of more serious particle agglomeration, poor particle hardness uniformity, and difficult control of particle morphology of cerium dioxide precursor particles after high temperature calcination.
[0041] The suspension prepared from this type of spherical nano-cerium dioxide is used in the chemical mechanical planarization process of shallow trench isolation layers and interlayer dielectrics in integrated circuit manufacturing, as well as in the ultra-precision polishing of optical glass. It has higher material removal and planarization efficiency, lower surface defects, and higher selectivity for the polishing of nitrides in shallow trench isolation planarization. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0043] Figure 1 This is a morphology result diagram of the spherical nano-cerium dioxide prepared in Example 1 of the present application;
[0044] Figure 2 This is a morphology result diagram of the spherical nano-cerium dioxide prepared in Example 2 of the present application;
[0045] Figure 3 This is a morphology result diagram of the spherical nano-cerium dioxide prepared in Example 3 of the present application;
[0046] Figure 4 This is a morphology result diagram of the spherical nano-cerium dioxide prepared in Example 4 of the present application;
[0047] Figure 5 This is a morphology result diagram of cerium dioxide prepared in Comparative Example 1 of the present application;
[0048] Figure 6 This is a morphology result diagram of cerium dioxide prepared in Comparative Example 2 of the present application;
[0049] Figure 7 The schematic diagram is a flow chart of the preparation method of spherical nano-cerium dioxide of the present application. DETAILED DESCRIPTION
[0050] As used herein:
[0051] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0052] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0053] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0054] In these examples, parts and percentages are by mass unless otherwise indicated.
[0055] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0056] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0057] This application provides a method for preparing spherical nano-cerium dioxide. Figure 7 ,include:
[0058] S100: Preparation of cerium dioxide precursor: adding a composite precipitant solution to a cerium salt solution to react and obtain a cerium dioxide precursor, wherein the composite precipitant solution includes a soluble carbonate and an alkali solution.
[0059] The cerium salt solution may be a solution obtained by dissolving a soluble cerium salt in water and filtering, and the soluble cerium salt may be cerium chloride, cerium nitrate or ammonium cerium nitrate, etc.; the cerium salt solution may also be a solution obtained by dissolving an insoluble cerium salt in acid and filtering, and the insoluble cerium salt may be cerium carbonate, cerium oxalate or cerium hydroxide, etc. Preferably, the cerium ion concentration in the cerium salt solution is 0.1 to 1.5 mol / l.
[0060] In a preferred embodiment, a surfactant having a cerium oxide content of 0.05-0.5% is added to the cerium salt solution to form a film on the particle surface to make the particles smaller and spherical. The cerium oxide content in the surfactant can be, for example, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%. The surfactant includes an ionic surfactant and / or a non-ionic surfactant; preferably, the surfactant is selected from polyvinyl pyrrolidone; more preferably, the surfactant is selected from PVP-K30.
[0061] Wherein, the composite precipitant solution includes soluble carbonate and alkali solution, and the purpose of adding alkali solution to the composite precipitant solution is to make cerium into basic carbonate, a part of which generates cerium hydroxide to make the particles smaller. The molar concentration ratio of the soluble carbonate to the alkali solution in the composite precipitant solution is 1: (0.01-2.0), for example, it can be 1: 0.01, 1: 0.05, 1: 0.1, 1: 0.2, 1: 0.3, 1: 0.4, 1: 0.5, 1: 0.6, 1: 0.7, 1: 0.8, 1: 0.9, 1: 1.0, 1: 1.1, 1: 1.2, 1: 1.3, 1: 1.4, 1: 1.5, 1: 1.6, 1: 1.7, 1: 1.8, 1: 1.9 or 1: 2.0. Preferably, the carbonate concentration in the composite precipitant solution is 0.3-3 mol / l.
[0062] Preferably, the soluble carbonate is selected from ammonium bicarbonate or sodium bicarbonate; the alkali solution is selected from any one or more of ammonia water, secondary amines, tertiary amines, quaternary amines, sodium hydroxide, potassium hydroxide, alkali metals and alkaline earth metal hydroxides.
[0063] More preferably, the soluble carbonate is selected from ammonium bicarbonate; the alkali solution is selected from any one or more of ammonia water, secondary amine, tertiary amine, and quaternary amine. This can avoid the introduction of alkali metal and alkaline earth metal ion contamination during the chemical mechanical polishing of integrated circuits.
[0064] Wherein, a composite precipitant solution is added to a cerium salt solution to react and obtain a cerium dioxide precursor, including:
[0065] First, the prepared cerium salt solution is heated to 60-90°C under stirring conditions, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C.
[0066] The prepared composite precipitant solution is then added to the cerium salt solution under stirring at a flow rate of 5 to 30 ml / min. The flow rate of the composite precipitant solution can be, for example, 5 ml / min, 10 ml / min, 15 ml / min, 20 ml / min, 25 ml / min or 30 ml / min. Addition of the composite precipitant solution is stopped until the pH of the mixed solution of the cerium salt solution and the composite precipitant solution reaches 5.5 to 7.5. The pH can reach, for example, 5.5, 6.0, 6.5, 7.0 or 7.5.
[0067] Finally, the mixed solution of the cerium salt solution and the composite precipitant solution is kept warm and aged for 1 to 6 hours under stirring conditions, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours.
[0068] S200: hydrothermal crystallization of a cerium dioxide precursor: hydrothermally crystallize the cerium dioxide precursor to obtain crystallized cerium carbonate.
[0069] Among them, crystallization refers to the process of crystallization of cerium carbonate, which can be used to purify and separate cerium carbonate. Controlling the conditions of crystallization can change the particle size and purity of the obtained cerium carbonate.
[0070] The cerium dioxide precursor is subjected to hydrothermal crystallization to obtain crystallized cerium carbonate, comprising:
[0071] The cerium dioxide precursor mixed solution after the heat preservation and aging in step S100 is heated to 80-200° C. and heat-treated for 2-48 hours. The heating temperature can be, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, and the insulation time can be, for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, 36h, 37h, 38h, 39h, 40h, 41h, 42h, 43h, 44h, 45h, 46h, 47h or 48h. Preferably, the ceria precursor is heated to 120-200° C. and heat treated for 4-14 hours.
[0072] After the heat preservation is completed, the slurry is cooled naturally, and then washed repeatedly with high-purity water until the slurry conductivity is lower than 400 μs / cm. Then, the slurry is vacuum filtered and dried or spray dried to obtain fully crystallized cerium carbonate.
[0073] S300: calcining the crystallized cerium carbonate: calcining the crystallized cerium carbonate to obtain the spherical nano-cerium dioxide.
[0074] The crystallized cerium carbonate is calcined to obtain the spherical nano-cerium dioxide, comprising:
[0075] The crystallized cerium carbonate is calcined at 550-950° C. in an air atmosphere for 1-5 hours to obtain the spherical nano-cerium dioxide. The calcination temperature may be, for example, 550° C., 600° C., 650° C., 700° C., 750° C., 800° C., 850° C., 900° C. or 950° C.; and the calcination time may be, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.
[0076] The preparation method of spherical nano cerium dioxide provided by the present application uses a composite precipitant high temperature step-by-step synthesis process, which is easy to control, has high stability, and can accurately control the morphology and size of the synthesized particles. The crystallized cerium carbonate prepared using this process technology has the advantages of spherical particle morphology, nano-monodispersed characteristics, and good particle uniformity, and the particle morphology, size, and dispersion state of cerium carbonate will not change after high-temperature calcination treatment, and has genetic inheritance, and can accurately control the morphology of spherical nano cerium dioxide. Compared with the traditional process, it avoids the shortcomings of more serious particle agglomeration, poor uniformity of particle hardness, and difficult control of particle morphology of precursor particles after high-temperature calcination.
[0077] The present application also provides a quasi-spherical nano-cerium dioxide, which is prepared by the above-mentioned method for preparing quasi-spherical nano-cerium dioxide. The quasi-spherical nano-cerium dioxide has the advantages of quasi-spherical particle morphology, nano-monodisperse characteristics, and good particle uniformity.
[0078] Preferably, the specific surface area of the spherical nano-cerium dioxide is 4-40m 2 / g, for example, 4 to 10 m 2 / g, or 10-30m 2 / g, or 20-40m 2 / g, more specifically, for example, (5, 6, 8, 10, 12, 14, 15, 16, 18, 20, 22, 25, 26, 29, 30, 33, 35, 36, 38 or 40) m 2 / g.
[0079] Preferably, the spherical nano-cerium dioxide is a secondary particle formed by agglomeration of primary particles, and the D50 of the primary particles is 20-400nm, for example, 20-40nm, or 30-60nm, or 50-100nm, or 500-150nm, or 100-200nm, or 100-300nm, or 200-300nm. Or 300-400nm; the D50 of the secondary particles is 60-1000nm, for example, 60-100nm, or 100-300nm, or 200-300nm, or 300-500nm, or 400-600nm, or 500-800nm, or 600-1000nm.
[0080] The present application also provides a method for preparing a quasi-spherical nano-cerium dioxide suspension, wherein the quasi-spherical nano-cerium dioxide is prepared into a slurry with a solid content of 5 to 50%, a dispersant is added, and the quasi-spherical nano-cerium dioxide is deagglomerated and uniformly dispersed in a medium under the action of any mechanical force such as ultrasound, high-speed fluid collision or a sand mill, and the quasi-spherical nano-cerium dioxide suspension is obtained by filtering.
[0081] The dispersed grinding method adopted in the present application can better preserve the particle morphology and primary particle size of nano-cerium dioxide without destroying it to the greatest extent.
[0082] The present application also provides a quasi-spherical nano-cerium dioxide suspension, which is prepared by the above-mentioned method for preparing a quasi-spherical nano-cerium dioxide suspension; the quasi-spherical nano-cerium dioxide in the suspension has a dispersion index of 0.20 to 0.80.
[0083] The suspension prepared from this type of spherical nano-cerium dioxide is used in the chemical mechanical planarization process of shallow trench isolation layers and interlayer dielectrics in integrated circuit manufacturing, as well as in the ultra-precision polishing of optical glass. It has higher material removal and planarization efficiency, lower surface defects, and higher selectivity for the polishing of nitrides in shallow trench isolation planarization.
[0084] The present application also provides the use of the above-mentioned spherical nano-cerium dioxide in chemical mechanical polishing, ultraviolet sun protection, catalysts, ceramic preparation, and surface polishing of glass and gemstone crystals.
[0085] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0086] Example 1
[0087] S1. Preparation of cerium dioxide precursor: a) Weigh 217.06g of cerium nitrate hexahydrate (0.5mol), dissolve it in 1000g of high-purity water, filter it and add it to a 3-liter semi-enclosed jacketed glass reactor, heat it to 85 degrees under 120-600RPM stirring, and add PVP-K30 with a cerium dioxide content of 0.15% to react. b) Weigh 142.308g of high-purity ammonium bicarbonate (0.9mol), 126g of 28% ammonia solution (1.8mol) and dissolve it in a 2-liter container, and add it to the cerium nitrate solution at a flow rate of 5ml / min under the same stirring conditions until the solution pH = 7.5, and then stop adding, and keep warm and age for 4 hours under the same stirring, temperature and pressure.
[0088] S2. Hydrothermal crystallization of cerium dioxide precursor: The cerium dioxide precursor solution prepared in step S1 is transferred as a whole to a 3-liter high-temperature and high-pressure reactor, heated to 120°C for 24 hours, cooled naturally, and then repeatedly washed with high-purity water until the slurry conductivity is less than 400μs / cm. Then vacuum filtration and drying or spray drying are performed to obtain fully crystallized cerium carbonate.
[0089] S3. Calcination of crystallized cerium carbonate: The crystallized cerium carbonate obtained in step S2 is calcined at a maximum temperature of 550° C. in an air atmosphere for 5 hours to obtain the spherical nano-cerium dioxide powder of Example 1.
[0090] S4. The spherical nano-cerium dioxide powder obtained in step S3 is prepared into a slurry with a solid content of 30%, and a dispersant is added to the slurry. The spherical nano-cerium dioxide powder is deagglomerated by a sand mill at the fastest possible flow rate to uniformly disperse the cerium dioxide in the liquid medium. Finally, pure water is added to dilute the solid content of the suspension to 10%, and the cerium dioxide suspension of Example 1 is obtained by precise filtration.
[0091] Example 2
[0092] S1. Preparation of cerium dioxide precursor: a) Weigh 108.53g of cerium nitrate hexahydrate, dissolve it in 1000g of high-purity water, filter it, add it to a 3-liter semi-enclosed jacketed glass reactor, heat it to 70 degrees under 120-600RPM stirring, and add PVP-K30 with a cerium dioxide content of 0.15% to react. b) Weigh 71.154g of high-purity ammonium bicarbonate and 12.6g of 28% ammonia solution in a 2-liter container, and add it to the cerium nitrate solution at a flow rate of 30ml / min under the same stirring conditions until the solution pH = 6, and then stop adding, and keep warm and age for 6 hours under the same stirring, temperature and pressure;
[0093] S2. Hydrothermal crystallization of cerium dioxide precursor: The cerium dioxide precursor solution prepared in step S1 is transferred as a whole to a 3-liter high-temperature and high-pressure reactor, heated to 200°C for 4 hours, cooled naturally, and then repeatedly washed with high-purity water until the slurry conductivity is less than 400μs / cm. Then vacuum filtration and drying or spray drying are performed to obtain fully crystallized cerium carbonate.
[0094] S3. Calcination of crystallized cerium carbonate: The crystallized cerium carbonate obtained in step S2 is calcined at a maximum temperature of 750° C. in an air atmosphere for 2 hours to obtain the spherical nano-cerium dioxide powder of Example 2.
[0095] S4. The spherical nano-cerium dioxide powder obtained in step S3 is prepared into a slurry with a solid content of 30%, and a dispersant is added to the slurry. The spherical nano-cerium dioxide powder is deagglomerated by a sand mill at the fastest possible flow rate to uniformly disperse the cerium dioxide in the liquid medium. Finally, pure water is added to dilute the solid content of the suspension to 10%, and the cerium dioxide suspension of Example 2 is obtained by precise filtration.
[0096] Example 3
[0097] S1. Preparation of cerium dioxide precursor: a) Weigh 434.12g of cerium nitrate hexahydrate, dissolve it in 1000g of high-purity water, filter it, add it to a 3-liter semi-enclosed jacketed glass reactor, heat it to 85 degrees under 120-600RPM stirring, and add PVP-K30 with a cerium dioxide content of 0.15% to react. b) Weigh 284.616g of high-purity ammonium bicarbonate and 12.6g of 28% ammonia solution in a 2-liter container, and add it to the cerium nitrate solution at a flow rate of 15ml / min under the same stirring conditions until the solution pH = 7.5, then stop adding, and keep warm and age for 2 hours under the same stirring, temperature and pressure;
[0098] S2. Hydrothermal crystallization of cerium dioxide precursor: The cerium dioxide precursor solution prepared in step S1 is transferred as a whole to a 3-liter high-temperature and high-pressure reactor, heated to 150°C for 14 hours, cooled naturally, and then repeatedly washed with high-purity water until the slurry conductivity is less than 400μs / cm. Then vacuum filtration and drying or spray drying are performed to obtain fully crystallized cerium carbonate.
[0099] S3. Calcination of crystallized cerium carbonate: The crystallized cerium carbonate obtained in step S2 is calcined at a maximum temperature of 550° C. in an air atmosphere for 5 hours to obtain the spherical nano-cerium dioxide powder of Example 3.
[0100] S4. The spherical nano-cerium dioxide powder obtained in step S3 is prepared into a slurry with a solid content of 30%, and a dispersant is added to the slurry. The spherical nano-cerium dioxide powder is deagglomerated by a sand mill at the fastest possible flow rate to uniformly disperse the cerium dioxide in the liquid medium. Finally, pure water is added to dilute the solid content of the suspension to 10%, and the cerium dioxide suspension of Example 3 is obtained by precise filtration.
[0101] Example 4
[0102] S1. Preparation of cerium dioxide precursor: a) Weigh 217.06g of cerium nitrate hexahydrate, dissolve it in 1000g of high-purity water, filter it, add it to a 3-liter semi-enclosed jacketed glass reactor, heat it to 75 degrees under 120-600RPM stirring, and add PVP-K30 with a cerium dioxide content of 0.15% to react. b) Weigh 142.308g of high-purity ammonium bicarbonate and 25.2g of 28% ammonia solution in a 2-liter container, and add it to the cerium nitrate solution at a flow rate of 10ml / min under the same stirring conditions until the solution pH = 7.5, and then stop adding, and keep warm and age for 4 hours under the same stirring, temperature and pressure;
[0103] S2. Hydrothermal crystallization of cerium dioxide precursor: The cerium dioxide precursor solution obtained in step S1 is transferred as a whole to a 3-liter high-temperature high-pressure reactor, heated to 180°C for 10 hours, cooled naturally, and then repeatedly washed with high-purity water until the slurry conductivity is less than 400μs / cm. Then vacuum filtration and drying or spray drying are performed to obtain fully crystallized cerium carbonate.
[0104] S3. Calcination of crystallized cerium carbonate: The crystallized cerium carbonate obtained in step S2 is calcined at a maximum temperature of 750° C. in an air atmosphere for 2 hours to obtain the spherical nano-cerium dioxide powder of Example 4.
[0105] S4. The spherical nano-cerium dioxide powder obtained in step S3 is prepared into a slurry with a solid content of 30%, and a dispersant is added to the slurry. The spherical nano-cerium dioxide powder is deagglomerated by a sand mill at the fastest possible flow rate to uniformly disperse the cerium dioxide in the liquid medium. Finally, pure water is added to dilute the solid content of the suspension to 10%, and the cerium dioxide suspension of Example 4 is obtained by precise filtration.
[0106] Comparative Example 1
[0107] S1. Preparation of cerium dioxide precursor: a) Weigh 217.06g of cerium nitrate hexahydrate, dissolve it in 1000g of high-purity water, filter it, add it into a 3-liter semi-enclosed jacketed glass reactor, and heat it to 85 degrees under stirring at 120-600RPM. b) Weigh 142.308g of high-purity ammonium bicarbonate and 0g of 28% ammonia solution in a 2-liter container, and add it to the cerium nitrate solution at a flow rate of 10ml / min under the same stirring conditions until the solution pH = 7.5, then stop adding, and keep warm and age for 4 hours under the same stirring, temperature and pressure.
[0108] S2. Hydrothermal crystallization of carbonate precursor: The carbonate precursor solution obtained in step S1 is transferred as a whole to a 3-liter high-temperature high-pressure reactor, heated to 180°C and heat-treated for 24 hours, cooled naturally, and then repeatedly washed with high-purity water until the slurry conductivity is less than 400μs / cm. Then vacuum filtration and drying or spray drying are performed to obtain fully crystallized cerium carbonate.
[0109] S3. Calcination of crystallized cerium carbonate: The crystallized cerium carbonate obtained in step S2 is calcined at a maximum temperature of 950° C. in an air atmosphere for 4 hours to obtain the nano cerium dioxide powder of Comparative Example 1.
[0110] S4. The nano-cerium dioxide powder obtained in step S3 is prepared into a slurry with a solid content of 30%, and a dispersant is added to the slurry. The slurry is deagglomerated by a sand mill at the fastest possible flow rate to uniformly disperse the cerium dioxide in the liquid medium. Finally, pure water is added to dilute the solid content of the suspension to 10%, and the cerium dioxide suspension of comparative example 1 is obtained by precise filtration.
[0111] Comparative Example 2
[0112] S1. Preparation of cerium dioxide precursor: a) Weigh 217.06g of cerium nitrate hexahydrate, dissolve it in 1000g of high-purity water, filter it, add it into a 3-liter semi-enclosed jacketed glass reactor, and heat it to 65 degrees under stirring at 120-600RPM. b) Weigh 142.308g of high-purity ammonium carbonate and 0g of 28% ammonia solution in a 2-liter container, and add it to the cerium nitrate solution at a flow rate of 10ml / min under the same stirring conditions until the solution pH = 7.0, and then stop adding, and keep warm and age for 6 hours under the same stirring, temperature and pressure.
[0113] S2. Hydrothermal crystallization of cerium dioxide precursor: The cerium dioxide precursor solution obtained in step S1 is transferred as a whole to a 3-liter high-temperature high-pressure reactor, heated to 180°C for 24 hours, cooled naturally, and then repeatedly washed with high-purity water until the slurry conductivity is less than 400μs / cm. Then vacuum filtration and drying or spray drying are performed to obtain fully crystallized cerium carbonate.
[0114] S3. Calcination of crystallized cerium carbonate: The crystallized cerium carbonate obtained in step S2 is calcined at a maximum temperature of 950° C. in an air atmosphere for 4 hours to obtain the nano cerium dioxide powder of Comparative Example 2.
[0115] S4. The nano-cerium dioxide powder obtained in step S3 is prepared into a slurry with a solid content of 30%, and a dispersant is added to the slurry. The slurry is deagglomerated by a sand mill at the fastest possible flow rate to uniformly disperse the cerium dioxide in the liquid medium. Finally, pure water is added to dilute the solid content of the suspension to 10%, and the cerium dioxide suspension of comparative example 2 is obtained by precise filtration.
[0116] The cerium dioxide suspension obtained in each embodiment and comparative example was subjected to SEM analysis to observe the particle morphology. The SEM analysis equipment used was a Sigma 500 field emission scanning electron microscope produced by Zeiss, Germany.
[0117] The results are as follows Figures 1 to 6 ,in Figures 1 to 4 They are the morphology images of the cerium dioxide suspensions of Examples 1 to 4, Figure 5 and Figure 6 The morphology of the cerium dioxide suspensions of Comparative Example 1 and Comparative Example 2 are shown respectively. Figures 1 to 4 The results show that in the cerium dioxide suspension obtained by the present application, the cerium dioxide has a spherical particle morphology, nano-monodisperse characteristics, good particle uniformity, and the particles will not agglomerate. However, in the cerium dioxide suspensions obtained by the schemes of comparative examples 1 and 2, the cerium dioxide has serious particle agglomeration, poor particle hardness uniformity, and difficult to control particle morphology.
[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0119] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing spherical nano-cerium dioxide, characterized in that: include: Preparation of cerium dioxide precursor: heating the cerium salt solution to 60-90°C, adding the composite precipitant solution to the cerium salt solution at a flow rate of 5-30 mL / min, stopping adding the composite precipitant solution until the pH of the mixed solution reaches 5.5-7.5, keeping warm and aging for 1-6 hours, adding a surfactant with a cerium dioxide content of 0.05-0.5% to the cerium salt solution, the surfactant is selected from PVP-K30, the composite precipitant solution includes a soluble carbonate and an alkali solution, the soluble carbonate is selected from ammonium bicarbonate, the alkali solution is selected from ammonia water, and the molar concentration ratio of the soluble carbonate to the alkali solution in the composite precipitant solution is 1: (0.01-2.0); Hydrothermal crystallization of a cerium dioxide precursor: hydrothermally crystallizing the cerium dioxide precursor to obtain crystallized cerium carbonate; Calcination of crystallized cerium carbonate: calcining the crystallized cerium carbonate to obtain the spherical nano-cerium dioxide.
2. The method for preparing spherical nano-cerium dioxide according to claim 1, characterized in that: The cerium ion concentration in the cerium salt solution is 0.1-1.5 mol / L; The carbonate concentration in the composite precipitant solution is 0.3-3 mol / L.
3. The method for preparing spherical nano-cerium dioxide according to claim 1, characterized in that: The preparation method includes at least one of the following features: a. The cerium dioxide precursor is subjected to hydrothermal crystallization to obtain crystallized cerium carbonate, comprising: The cerium dioxide precursor is heated to 80-200° C. and heat treated for 2-48 hours; Cooling, washing and drying to obtain the crystallized cerium carbonate; b. calcining the crystallized cerium carbonate to obtain the spherical nano-cerium dioxide, comprising: The crystallized cerium carbonate is calcined in an air atmosphere at 550-950° C. for 1-5 hours to obtain the spherical nano-cerium dioxide.
4. A spherical nano-cerium dioxide, characterized in that: Prepared by the preparation method of spherical nano-cerium dioxide according to any one of claims 1 to 3; The spherical nano-cerium dioxide comprises at least one of the following features: a. The specific surface area of the spherical nano-cerium dioxide is 4-40m 2 / g; b. The spherical nano-cerium dioxide is a secondary particle formed by agglomeration of primary particles, and the D50 of the primary particles is 20 to 400 nm; c. The D50 of the secondary particles is 60-1000nm.
5. A method for preparing a spherical nano-cerium dioxide suspension, characterized in that: The spherical nano-cerium dioxide described in claim 4 is prepared into a slurry with a solid content of 5-50%, and a dispersant is added to deagglomerate the spherical nano-cerium dioxide and evenly disperse it in a medium under the action of any mechanical force such as ultrasound, high-speed fluid collision or a sand mill, and the spherical nano-cerium dioxide suspension is obtained by filtering.
6. A spherical nano-cerium dioxide suspension, characterized in that: The spherical nano-cerium dioxide suspension is prepared by the method for preparing the spherical nano-cerium dioxide suspension described in claim 5; the spherical nano-cerium dioxide in the suspension has a dispersion index of 0.20 to 0.
80.
7. Use of the spherical nano-cerium dioxide according to claim 4 in chemical mechanical polishing, ultraviolet sun protection, catalyst, and ceramic preparation.
Citation Information
Patent Citations
Preparation method of cerium oxide and CMP polishing solution containing cerium oxide abrasive
CN105800660A
